The micro-politics of organisational change in professional youth football: Towards an understanding of "actions, strategies and professional interests" - Gibson, L.; Groom, R. (International Journal of Sports Science & Coaching, 2019)
Employment within professional football is characterised by high levels of staff turnover, uncertainty, vulnerability and insecurity. This paper aims to investigate the experiences of James, Head of Foundation Phase within an English professional youth academy, during a period of organisational change. Data were collected through field notes, informal observations and meetings, formal academy team meetings, co-worker interviews and four semi-structured in-depth participant interviews, which were subjected to an iterative process of inductive and deductive analysis. Theorising regarding the influence of professional self-interests upon the actions and strategies of the social actors was utilised to make sense of James' narrative. The findings highlighted how James strategically managed his relationships with others to further his own professional self-interests. Finally, following the findings of this study, we propose that the ability to develop micro-political literacy and a repertoire of micro-political actions and strategies would benefit coaches working within professional football during such periods of instability and change.